Left ventricular mass and left ventricular mass index in normal malay primary school children. - Mat Arifin, Fazila (2012)
Left ventricular mass (LVM) and Left ventricular mass Index (LVMI) are two parameters that are considered important in predicting the outcomes of cardiovascular diseases in adults. Even though there are a lot of interest in the problem of left ventricular hypertrophy in children,there is relatively little published data on normal values of the left ventricular mass (LVM) during the developmental age.